Unity of Sciences (UoS) as a Paradigm For Indonesian Islamic Family Law Reconstruction. - Abdillah, Junaidi; Nuriyyatiningrum, Mahdaniyal Hasanah; Miftahunnaja, Nafila Inarotussofia (Universitas Islam Negeri Raden Intan Lampung, 2022)
Unity of Sciences (UoS) as a Paradigm For Indonesian Islamic Family Law Reconstruction. This article aims to examine the use of the Unity of Sciences (UoS) application in efforts to reconstruct family law in Indonesia. This is because the existence of Islamic family law in this country has gained a good place in people's lives, evidenced by the transformation of several al-ahwāl al-shakhsyiyah’s (Islamic Family Law) materials into national law. This transformation, even though it implies a renewal entity, however, at the same time, it draws a lot of criticism from some circles, ranging from constructive to deconstructive criticism. This study is a research library that uses a philosophical approach and a siyāsah shar'iyyah‘s (Islamic politics of Law) perspective. The data were obtained through document-juridical sources which were then analyzed using inductive analysis and critical reflection. This study concludes that the characteristics of Islamic family law reform in the form of statutory regulations have used a reformative approach and burhāni reasoning. In addition, to respond to and anticipate the dynamics and legal changes that are profane in nature, Islamic law requires a Unity of Sciences (UoS) approach so that Islamic law can be grounded in Indonesia.